Investigating a Protective Role for Parkin Downstream of Dopamine Stress in In-Vitro Cell Models - Hassan, Nazia (Université d'Ottawa / University of Ottawa, 2025)
Parkinson's disease (PD) is characterized by the progressive loss of dopaminergic neurons in the Substantia nigra pars compacta (SNc), a region particularly vulnerable to dopamine (DA) metabolite toxicity and oxidative stress. Mutations in the PRKN gene, which encodes parkin, an E3 ubiquitin ligase thought to be important for mitophagy, underlie what is known as autosomal recessive, early-onset PD (EOPD). In parkin-linked PD, the loss of DA-producing neurons is relatively selective for SNc and Locus coeruleus (LC) neurons, highlighting parkin's crucial role in protecting them. Recent studies from our lab have shown that parkin also plays an antioxidant role, protecting DA-producing neurons from oxidative damage by reducing reactive oxygen species (ROS) and sequestering DA-derived radicals. This protective action leads to parkin's own oxidation and subsequent insolubility. Notably, this shift to an insoluble state has been shown to impair parkin's E3 ligase function, suggesting that parkin's protective role under oxidative stress conditions may be independent of its role in mitophagy. Furthermore, in normal human brain, parkin has been found to associate with neuromelanin (NM), a pigment formed in catecholaminergic neurons via the sequestration of toxic DA radicals, as well as with CD63-positive lysosomal vesicles, suggesting a role for parkin in lysosomal pathways that mitigate cellular damage. In this study, I aimed to investigate how DA-induced cellular stress affects parkin's oxidation, solubility, and localization within the cell, with a particular interest in its interaction with NM and CD63. To explore this, I used two models of DA-linked stress. The first model involved the direct addition of DA to the culture medium to simulate oxidative stress from DA auto-oxidation. The second model utilized tyrosinase cDNA transfection in M17 neuroblastoma cells to drive intracellular melanin synthesis, creating a controlled system for examining parkin's interactions with melanin. There, melanin synthesis arises from the formation of DA oxidation products via tyrosinase activity. My results showed that DA treatment led to partial oxidation and insolubilization of parkin, particularly when the antioxidant glutathione was depleted by using buthionine sulfoximine (BSO), which exacerbates oxidative stress. These modifications were not associated with any visible co-localization by wild-type (WT) parkin with CD63 in M17 cells or microscopically visible aggregate formation. Unexpectedly, parkin remained dispersed throughout the cell post DA-treatment. In the tyrosinase model, parkin did not undergo any significant changes in oxidation or solubility with increasing melanin accumulation, nor did parkin visibly co-localize with melanin granules. However, cells expressing parkin showed accelerated melanin formation compared to those without. Overall, this study explored the behavior of parkin under DA-induced stress conditions in an undifferentiated, human M17 neuroblastoma cell culture system. While parkin does undergo oxidative changes, these results suggested that the extent of these changes - along with parkin's solubility and localization - are highly dependent on the chosen cell model and experimental conditions employed. The cellular environment, as determined by factors, such as the capacity to neutralize endogenous as well as exogenously added DA metabolites, likely plays a role in shaping parkin's response to stress. These findings emphasize the need for further investigation into how parkin behaves in different neural models to better understand its role in protecting dopaminergic neurons, particularly in the context of brain ageing, which will likely inform the pathogenesis of EOPD, and possibly of sporadic PD.
Keywords: Parkin; Parkinson's Disease; Dopamine